Design of Networked Multiplayer Snake and Ladder Educational Game Based on Hash Map and Vector Data Structure - A'la Syauqi; Permata Rahmatul Hijjah (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2020)
Computer games have been used as educational media or popularly named as educational games. However, most educational computer games that have been created can be played by one player. This study aims to build a multiplayer ladder and snake educational game focused on the server program as a moderator that handles players, player groups, and data traffic during the game is running. The game is built on Java socket programming and local area network (LAN) as a data communication medium between players. Whereas to handle the username and socket address of the whole player, the hash map data structure is used. A vector data structure is also used to manage data package sending for each player group. The experiment shows that the system works properly where the computer server’s performance is influenced by the specifications, especially the processor and random-access memory (RAM).